Emerging Disinfection Technologies In Infection Control: A Review Of Nano-Silver And Ozone-Based Approaches (The Review of Diabetic Studies, 2024)
Nano-silver and ozone-based disinfection technologies have emerged as promising alternatives to traditional methods for infection control in healthcare settings. This review explores the scientific basis, mechanisms of action, applications, efficacy, and safety considerations of these technologies. Nano-silver exerts broad-spectrum antimicrobial activity through the release of silver ions and generation of reactive oxygen species, disrupting microbial cell membranes and DNA. Its incorporation into medical devices, textiles, and surface coatings provides sustained protection against pathogens. Ozone, a powerful oxidant, rapidly inactivates microorganisms by attacking cell walls and viral capsids. Its gaseous form allows comprehensive disinfection of air, water, and surfaces. Both technologies demonstrate efficacy against multidrug-resistant bacteria, viruses, and fungi, offering advantages over conventional disinfectants. However, challenges include potential cytotoxicity, environmental impact, and the need for standardized testing protocols. Integration of these technologies into infection control programs requires careful implementation, staff training, and compatibility with existing multi-barrier strategies. Future research should focus on developing composite systems, controlled-release nanomaterials, and eco-friendly approaches. Clinical trials are needed to validate their real-world impact on reducing healthcare-associated infections. As the threat of antimicrobial resistance grows, nano-silver and ozone-based disinfection offer promising tools for enhancing infection prevention and control in healthcare facilities.